SANATIVE EFFECT OF MULTIHERBAL FORMULATION – AKSS16-LIV01 ON CCL4-INDUCED HEPATIC DYSFUNCTION IN MICE - DARBAR, SOUMENDRA; SAHA, SRIMOYEE; PRAMANIK, KAUSIKISANKAR; CHATTOPADHYAY, ATISKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Hepatic dysfunction is a critical public health problem affecting the global population, characterized by excessive deposition of extracellular matrix components due to increased matrix production and decreased matrix degradation. The present work was aimed to evaluate hepatoprotective effect of AKSS16-LIV01 a newly developed multiherbal formulation against carbon tetrachloride (CCl4)-induced liver dysfunction in Swiss albino mice to establish it as a bench to bedside formulation catering to the various facets of hepatic malfunction. Methods: Thirty-six Swiss adult albino Wister mice divided into six groups. Group-I control untreated animals, Group-II received AKSS16-LIV01 (400 mg/kg), Group-III received CCl4 (1 ml/kg-bw), Group-IV received AKSS16-LIV01 (200 mg/kg) after 2 weeks CCl4 induction, Group-V received AKSS16-LIV01 (400 mg/kg) after 2 weeks CCl4 induction, and Group-VI received standard drug silymarin (100 mg/kg). At the end of the experimental period, all the animals were fasted overnight and blood was collected through retro-orbital plexus for preparation of serum and was analyzed for biochemical parameters, lipid profile, and total plasma protein. Liver tissue was collected for histological study. Results: The combined plant extract including six Indian medicinal herbs and three medicinal spices (AKSS16-LIV01) showed significant hepatoprotective effect by controlling the various essential biochemical parameters in serum. Moreover, treatment with AKSS16-LIV01 raised the level of serum total protein, normalizes the serum biochemical and lipid profiles parameters. Pre-treatment with AKSS16-LIV01 in mice also restored the alteration of various liver parameters such as aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, gamma-glutamyl transferase, blood urea nitrogen, total bilirubin, and direct bilirubin on CCl4-induced liver damage. Gross liver morphology and normal histological examination of the liver also supported hepatic protection by AKSS16-LIV01. Conclusion: Taken together, these results suggest that AKSS16-LIV01 may induce remarkable protective effects against hepatic injury induced by CCl4 treatment.